2023
DOI: 10.1093/oncolo/oyad139
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Talazoparib in Patients With Germline BRCA1/2 Mutation-Positive, Early-Stage Triple-Negative Breast Cancer: Results of a Phase II Study

Abstract: Background The undetermined efficacy of the current standard-of-care neoadjuvant treatment, anthracycline/platinum-based chemotherapy, in patients with early-stage triple-negative breast cancer (TNBC) and germline BRCA mutations emphasizes the need for biomarker-targeted treatment, such as poly(ADP-ribose) polymerase inhibitors, in this setting. This phase II, single-arm, open-label study evaluated the efficacy and safety of neoadjuvant talazoparib in patients with germline BRCA1/2-mutated ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…In the phase II study, talazoparib monotherapy elicited pCR rates that were comparable to those observed with combination anthracycline and taxane-based chemotherapy regimens when used in the neoadjuvant settings in patients with BRCA1/2 positive, early HER2-negative BC ( 114 ). In the phase II single-arm NEOTALA trial, talazoparib yielded promising pCR rates in patients with BRCA mutated early BC comparable to those historically observed with combination anthracycline- and taxane-based chemotherapy regimens ( 115 ).…”
Section: Management Of Brca -Mutated Early-stage B...mentioning
confidence: 86%
“…In the phase II study, talazoparib monotherapy elicited pCR rates that were comparable to those observed with combination anthracycline and taxane-based chemotherapy regimens when used in the neoadjuvant settings in patients with BRCA1/2 positive, early HER2-negative BC ( 114 ). In the phase II single-arm NEOTALA trial, talazoparib yielded promising pCR rates in patients with BRCA mutated early BC comparable to those historically observed with combination anthracycline- and taxane-based chemotherapy regimens ( 115 ).…”
Section: Management Of Brca -Mutated Early-stage B...mentioning
confidence: 86%
“…In the phase 2 NEOTALA trial, 24-week neoadjuvant talazoparib led to a pathologic complete response (pCR) rate of 53% in carriers of gBRCA1/2 variants with TNBC . This is similar to what was achieved with anthracycline-taxane–based neoadjuvant regimens, prior to the use of immune checkpoint inhibitors.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, all recruited patients had basal-like TNBC on the basis of immunohistochemistry assessments, and the patients in the non-basal group were excluded. Non-basal TNBCs, although triple negative, share few of the biological and genomic features of basal-like TNBC, and respond less well to most systemic treatments 20 22 . Therefore, their inclusion in randomized controlled trials of TNBC add non-informative data to the analyses that could affect results.…”
Section: Discussionmentioning
confidence: 99%
“…Of note however, more patients required a blood transfusion for treatment-induced anaemia with olaparib (51.4% versus 30.5%). High rates of symptomatic anaemia have also been described with the use of talazoparib monotherapy (39.3%) in the neoadjuvant setting 22 . Our data are therefore consistent with the known toxicity profile of PARP inhibitors, enhanced by the additional effect of platinum on the bone marrow.…”
Section: Discussionmentioning
confidence: 99%